THE RENAL LESION IN SYSTEMIC VASCULITIS - O.V. Syniachenko; T.B. Bevzenko; M.V. Iermolaieva; O.O. Diadyk (Ukrainian Journal of Nephrology and Dialysis, 2015)
The aim and the objectives: to investigate the frequency and the character of renal lesion in systemic vasculitis, as well as aspects of the pathogenesis of nephropathy in this category of patients.Material and methods: investigate 525 patients, including 193 - with vasculitis Shenlayna-Henoch, 116- with microscopic polyangiitis, 93 - with cryoglobulinemic vasculitis, 39 - with polyarteritis nodosa, 29 - with aortoarteritis Takayasu, 28 - withWegener’s granulomatosis and 27 - with eosinophilic vasculitis Churg-Strauss.Results: the renal lesion is observed in 52-68% cases of vasculitis depends on the age and the sex of the patients, the duration of the disease, the degree of activity of the pathological process, alteration in the heart and lungs, integrated severity extrarenal signs of the disease, at that, the rate ofprogression of nephropathy associated with the character of the disorders of the immune system, the rheological properties of blood and endothelial vessels’function.Conclusions: kidney disease is one of the leading signs of systemic vasculitis and observed in most patients, it is determine the course of the disease.